L-carnitine alleviates cardiac, hematological, biochemical, inflammatory and growth performance alterations in cold-stressed broiler chickens - Mokhtar Fathi; Shahriar Saeedian; Milad Zivdar; Fatimah Mirahmadi (Italian Journal of Animal Science)
This study was conducted to evaluate the potential of L-carnitine (LC) supplementation in alleviating the adverse effects of cold stress (CS) in broiler chickens. A total of 600 one-day-old male Ross 308 chicks were randomly assigned to six treatment groups with five replicates of 20 birds per pen. One group (100 birds) was maintained under thermoneutral (TN) conditions, while the remaining five groups (500 birds) were subjected to cold stress. Starting on day 14, the CS groups received either a control diet or diets supplemented with LC at levels of 30 (LC-30), 60 (LC-60), 120 (LC-120), or 240 mg/kg (LC-240). Results showed that LC supplementation significantly improved growth performance index, cardiac indices, including relative heart weight, right ventricle (RV) to total ventricle (TV) ratio, RV/body weight ratio, and reduced mortality due to ascites. It also enhanced plasma antioxidant enzyme activities—superoxide dismutase, catalase, and glutathione peroxidase—while decreasing malondialdehyde levels. Furthermore, dietary LC reduced the cold stress-induced elevation in pro-inflammatory cytokines (IL-6, IL-1β and TNF-α). Biochemical parameters were favourably modulated by LC supplementation, with reductions in ALT, AST, ALP, triglycerides, low density lipoprotein and triiodothyronine (T3), and increases in total protein, high density lipoprotein and thyroxine (T4) compared to the CS group. Hematological improvements included decreased RBC count, haemoglobin, haematocrit, heterophil percentage and H/L ratio, along with an increase in blood pH. In conclusion, dietary LC supplementation under cold stress conditions effectively mitigated performance, physiological, and metabolic disturbances, suggesting its potential as a protective nutritional strategy in broiler production.